Persepsi Siswa terhadap Pembaharuan Pembelajaran Studi Kasus di Madrasah Ibtidaiyah Muhammadiyah Bulu Manyaran Wonogiri - Setiawan, Rizka; Anshory, Isa (TSAQOFAH, 2024)
This research examines students' perceptions of the renewal of learning through habituation in the morning with student and female students' perceptions of the implementation of habituation (Dhuha Prayer, Memorizing Prayers, Memorizing Asmaul Husna, Singing Indonesia Raya Songs, Singing March Muhammadiyah) at Madrasah Ibtidaiyah Muhammadiyah Hair. The method used is the Case Method. The population of this study was Madrasah Ibtidaiyah Muhammadiyah Bulu students with respondents 20% of the total population. Data were collected using questionnaires, and the results of the research showed that 49% of respondents agreed with the reform of learning at Madrasah Ibtidaiyah Muhammadiyah Bulu, Punduhsari Village, Manyaran District, Wonogiri Regency.